Microinvasive Glaucoma Surgery in US Ophthalmology Residency: Surgical Case Log Cross-sectional Analysis and Proposal for New Glaucoma Procedure Classification. Issue 7 (July 2021) - Qiu, Mary; Woreta, Fasika A.; Boland, Michael V.
Abstract : Precis: A cross-sectional sample of the US ophthalmology residency graduating class of 2018 revealed that 18.4% of residents logged <5 traditional glaucoma surgeries, and 63.4% logged at least 1 microinvasive glaucoma surgery (MIGS). Purpose: Describe the state of MIGS in US ophthalmology residency training and propose a glaucoma procedure classification system for residents' surgical case logs. Methods: Deidentified case logs from residents graduating in 2018 were requested from US residency program directors. Results: Case logs were received for 152/488 (31%) residents from 36/115 (31%) programs. The mean number of traditional glaucoma surgeries per resident was 9.0±5.9 (range: 0 to 31). The mean number of MIGS per resident was 5.2±8.9 cases (range: 0 to 58). There were 28/152 (18.4%) residents from 16/36 (44.4%) programs who logged <5 traditional glaucoma surgeries as primary surgeon, and 3/152 (2.0%) residents from 3/36 (8.3%) programs who logged zero traditional glaucoma surgeries as primary surgeon. There were 98/152 (64.5%) residents from 32/36 (88.8%) programs who logged <5 MIGS as primary surgeon, and 48/152 (31.6%) residents from 25 of 36 (69.4%) programs who logged zero MIGS as primary surgeon. There were 104/152 (63.4%) residents from 33/36 (91.6%) programs who logged at least 1 MIGS as primary surgeon; there were 3/36 (8.3%) residency programs where no resident logged any MIGS as primary surgeon. Conclusions: US ophthalmology residents' MIGS experience varies widely. Residents can satisfy glaucoma surgery requirements with some MIGS, even in the absence of adequate traditional glaucoma surgeries. We propose a residency case log classification system that better reflects the growing role of MIGS in clinical practice and helps ophthalmic educators more accurately track procedures requiring related skills. Abstract : Supplemental Digital Content is available in the text.